E-incentives for the online consumer : a comprehensive study. - Lui, Clarinda Ya Ying. (2008)
An in-depth study of the multi-faceted effects of E-incentives, the online version of traditional sales promotions. Includes study of impact of E-incentives on purchase behavior, customer attraction, satisfaction and loyalty.